2018
DOI: 10.3390/nu10040494
|View full text |Cite
|
Sign up to set email alerts
|

Post-Game High Protein Intake May Improve Recovery of Football-Specific Performance during a Congested Game Fixture: Results from the PRO-FOOTBALL Study

Abstract: The effects of protein supplementation on performance recovery and inflammatory responses during a simulated one-week in-season microcycle with two games (G1, G2) performed three days apart were examined. Twenty football players participated in two trials, receiving either milk protein concentrate (1.15 and 0.26 g/kg on game and training days, respectively) (PRO) or an energy-matched placebo (1.37 and 0.31 g/kg of carbohydrate on game and training days, respectively) (PLA) according to a randomized, repeated-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 96 publications
7
34
1
5
Order By: Relevance
“…Hs-CRP concentration was quantitatively measured in serum with a latex-enhanced immunoturbidimetric assay, using the Roche Cobas clinical chemistry analyzer, as described [ 42 ]. TBARS, PC, TAC, CAT, GSH and GSSG were assayed according to protocols previously described [ 36 , 43 , 44 , 45 , 46 , 47 ]. Briefly, for the determination of TBARS 100 μL of serum were mixed with 500 μL 35% TCA and 500 μL Tris-HCL (200 mM; pH 7.4) and incubated at room temperature for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hs-CRP concentration was quantitatively measured in serum with a latex-enhanced immunoturbidimetric assay, using the Roche Cobas clinical chemistry analyzer, as described [ 42 ]. TBARS, PC, TAC, CAT, GSH and GSSG were assayed according to protocols previously described [ 36 , 43 , 44 , 45 , 46 , 47 ]. Briefly, for the determination of TBARS 100 μL of serum were mixed with 500 μL 35% TCA and 500 μL Tris-HCL (200 mM; pH 7.4) and incubated at room temperature for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Protein supplementation has been shown to expedite skeletal muscle protein turnover by upregulating muscle protein synthetic rate under conditions of increased physiological stress that would otherwise favour negative protein balance, such as those applied during a congested soccer schedule [36,83]. In a recent study, Poulios et al [88] provided evidence that protein feeding may be advantageous for eccentric and concentric lower limb muscle strength and high-speed running performance, whilst also allowing faster recovery of protein and lipid peroxidation during a congested schedule. Other studies suggest that, recovery from injury typically requires additional protein [112], gelatin or hydrolysed collagen [31].…”
Section: Proteinmentioning
confidence: 99%
“…Souglis et al [106] observed that both male and female players had elevated blood uric acid and creatine kinase concentrations 4-5 days after competitive soccer matches. Therefore, nutrition strategies should also target recovery from muscle damage sustained during training or match play [88].…”
Section: Post-match Nutritionmentioning
confidence: 99%
“…Individuals must be cautious when attempting to measure recovery from exercise based on these metrics alone. For example, a recent study of 20 high-level soccer players tested the effects of a milk protein concentrate supplement (80% casein and 20% whey) compared to an isocaloric carbohydrate-containing placebo on high intensity running performance, knee extensor and flexor strength, and antioxidative capacity over the course of a 1-week in-season microcycle consisting of two games separated by 2 days ( 53 ). On game days (days 1 and 4), the supplement was consumed immediately post-, 3 h post-, and 6 h post-match in three different doses of 25, 30, and 25 g, respectively, resulting in a total of 80 g. On training days (days 2, 3, 5, and 6), 20 g of the supplement was consumed with breakfast.…”
Section: Protein Supplementation and Endurance Trainingmentioning
confidence: 99%